ADJEKTIVA BERTARAF DAN TIDAK BERTARAF PADA HARIAN RIAU POS KAJIAN SEMANTIK DAN SINTAKSIS - Umami, Marisa Tri; Mustafa, M.Nur; ', Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study discusses the adjective class and class tisak in Riau Pos daily. This study included into the semantic and syntactic studies. This study used a qualitative approach and descriptive method that aims to describe the meaning and function of adjectives standard and not standard in Riau Pos daily especially the February issue of 2014. The subject of research in the form of adjectives found in Riau Pos daily edition of February 2014. This study took the form of data terturlis where the data is taken from 28 newspapers commencing from February 1 to February 28. Data obtained using the documentation techniques. Researchers took the data and classify the data into standard types of adjectives, adjectives are not standard and rated adjectives. Once data is classified, the researchers analyzed the functions contained in the daily adjectives Riau Pos Edis February 2014. Based on data analysis, research concluded that the Riau Pos daily edition of February 2014 are standard Adjectives, adjectives are not standard, and rated adjectives used in Riau Daily Post adjectives February 2014 edition of the most widely used standard is the adjective size fourteen pieces. Adjective not used in the standard of at least daily post riau February 2014 edition of five pieces. Type rated adjective most used in Riau daily post february 2014 edition is based on the level of quality is the level elatif some fifteen pieces while based on the level of comparison is the comparative level and the level of equational number five. Function attributive adjective most diguakan by sua number-one level. Predicative functions not found in the adjectives are not standard in Riau Daily Post edition of February 2014. The most widely used adverbial function at the level of the quality of a number of twenty-one. Adverbial adjectives and most widely used in this study a number of forty-six.Keywords: standard adjective, adjective is not standard, Riau Pos daily